Rapid and efficient removal of methylene blue by freshly prepared manganese dioxide. Issue 1 (1st January 2017) - Qin, Qingdong; Sun, Tian; Yin, Wanyun; Xu, Yan
Abstract: Freshly prepared manganese dioxide was employed as an adsorbent to remove methylene blue (MB) from water. It was demonstrated that the obtained MnO2 outperformed several adsorbents previously reported in the literatures for a rapid and effective removal of MB. The time required to reach adsorption equilibrium was as short as 2 min. The Langmuir isotherm fit well into the experimental data with a linear correlation coefficient ( R 2 ) of 0.997. The maximum adsorption capacity was 627.1 mg/g. The removal efficiency of MB increased along with increasing MnO2 dose, whereas decreased over pH 3.0–6.0. The adsorption mechanism was primarily attributed to electrostatic attraction.